2019
DOI: 10.1080/00207284.2019.1656078
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating an Experiential Group in an Educational Environment: Managing Dual Relationships

Abstract: The significant benefit of experiential learning in group work presents ethical complexities that must be considered by students, faculty, and programs. This article explores the clinical and ethical intricacies of teaching a group counseling course while facilitating an experiential group as part of the course curriculum. Specifically, the framework presented examines the dual roles of facilitator and instructor as complementary versus adversarial functions while analyzing challenges to both teacher and stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 37 publications
2
14
0
Order By: Relevance
“…That is, being part of an EGG during their formalized training allowed them to gain richer perspectives as to what clients might experience when they first enter treatment and practice giving/taking feedback. The present study supports other findings (Haber & Deaton, 2019) regarding the reported developmental benefits of EGGs in group therapy training.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…That is, being part of an EGG during their formalized training allowed them to gain richer perspectives as to what clients might experience when they first enter treatment and practice giving/taking feedback. The present study supports other findings (Haber & Deaton, 2019) regarding the reported developmental benefits of EGGs in group therapy training.…”
Section: Discussionsupporting
confidence: 93%
“…might experience when they first enter treatment and practice giving/taking feedback. The present study supports other findings (Haber & Deaton, 2019) regarding the reported developmental benefits of EGGs in group therapy training.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Psychiatry trainees are frequently in contact outside the group experience as colleagues on the wards or in the classroom, friends, or romantic partners. Interpersonal conflict or self-disclosure in the process group may adversely affect work and personal relationships [ 19 ]. Even when participation is explicitly voluntary, there may be unspoken social consequences of not participating.…”
Section: Recommendations For Training Program Directorsmentioning
confidence: 99%
“…After completing the initial planning, we recommend that programs provide trainees with an orientation guide that includes a rationale, learning objectives, and group agreements for participation [ 19 ]. Ideally, these guidelines are reviewed with both the program director and the group leader together.…”
Section: Recommendations For Training Program Directorsmentioning
confidence: 99%